Prenatal Diagnosis of Monosomy 17p (17p 13.3 → pter) Associated With Polyhydramnios, Intrauterine Growth Restriction, Ventriculomegaly, and Miller-Dieker Lissencephaly Syndrome in a Fetus - Chin-Yi Lin; Chih-Ping Chen; Chiung-Ling Liau; Pen-Hua Su; Teng-Fu Tsao; Tung-Yao Chang; Wayseen Wang (Elsevier, 2009)
Objective: To present the prenatal magnetic resonance imaging (MRI) and ultrasound findings of Miller-Dieker lissencephaly syndrome (MDLS) associated with chromosome 17p13.3 deletion in a fetus. Case Report: A 30-year-old, primigravid woman was referred to the hospital at 31 weeks' gestation because of intrauterine growth restriction (IUGR) and polyhydramnios detected by ultrasound. The pregnancy was uneventful until 31 weeks of gestation when IUGR and polyhydramnios were first noted. Level II ultrasound at 31 weeks' gestation showed fetal biometry equivalent to 27 weeks' gestation, an amniotic fluid index of 33.4 cm, ventriculomegaly, and abnormal sulcal development with absence of gyri and sulci, and a shallow Sylvian fissure. Other organs were unremarkable. Subsequent amniocentesis revealed a 46,XY,del(17)(p13.3) karyotype. Ultrafast fetal MRI performed at 34 weeks of gestation revealed agyria/pachygyria, a figure-eight appearance of the brain, a wide and shallow Sylvian fissure, enlarged subarachnoid space, ventriculomegaly, and polyhydramnios. At 35 weeks' gestation, a 1,346-g male baby was delivered with facial dysmorphism, characteristic of MDLS. Postnatal MRI confirmed the prenatal diagnosis. Conclusion: Polyhydramnios, IUGR and ventriculomegaly are important prenatal ultrasound markers of MDLS. Prenatal diagnosis of these markers should include a detailed investigation of cerebral sulci and fissures, and genetic analysis for MDLS. Fetal MRI is helpful for the diagnosis of lissencephaly.